Needs Analysis for developing augmented reality-based critical reading materials for EFL students - Ida Yulianawati; Zubaedah Wiji Lestari; Syafryadin Syafryadin; Natalia Anggrarini (Studies in English Language and Education, 2025)
English has been a compulsory subject in higher education across Indonesia. However, concerns about students proficiency remain widespread. Despite the importance of integrating technology into English instruction, especially for enhancing critical reading and thinking skills, many teachers still rely on intuition rather than a systematic needs analysis when developing teaching materials. Consequently, the content often fails to address learners actual needs or improve language mastery effectively. This study aims to explore the specific needs and challenges EFL students face in developing critical reading skills and their perceptions of augmented reality (AR)-based materials used in such classes. A mixed-methods approach was employed, involving surveys and interviews with 79 purposively selected students from two private universities in West Java, Indonesia. Findings revealed that students commonly use online platforms as sources for critical reading activities. They acknowledged the importance of critical reading and expressed that AR significantly enhanced their engagement and fostered independent learning. Pedagogical advantages of AR-based materials included promoting multisensory learning, improving students critical literacy and confidence, increasing enjoyment, and supporting a student-centered approach to technology. Additionally, AR allowed for the integration of virtual and real-world element in meaningful learning environments, which helped reduce cognitive load. The students also recognized ARs role in expanding access to education by making learning experiences more inclusive, engaging, and responsive to diverse learning preferences. Overall, AR-based materials were perceived as a valuable tool to support the development of critical reading skills in English language education.